2017
DOI: 10.4314/jfas.v9i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum-hydrocarbons biodegradation by <i>Pseudomonas</i> strains isolated from hydrocarbon-contaminated soil

Abstract: Many indigenous microorganisms in water and soil are capable of degrading hydrocarbon contaminants. In this study, two bacterial strains were isolated from a contaminated soil of a refinery of Arzew (Oran). The isolated strains were identified as Pseudomonas aeruginosa (P3) and Pseudomonas fluoresens (P4). The capability of these isolates to degrade petroleum was performed by measuring the optical density, colony forming unit counts (CFU/ml) and concentration of total petroleum hydrocarbons (TPH). Degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The presence of these species in polluted environments is due to their ability to tolerate and use pollutants as a source of carbon and energy [27]. Most of these strains have already been identified in environments polluted by hydrocarbons [10,[27][28][29]. Liang et al (2014) also identified a strain of Pseudomonas sp.…”
Section: Characterization Of Gram-bacteriamentioning
confidence: 99%
“…The presence of these species in polluted environments is due to their ability to tolerate and use pollutants as a source of carbon and energy [27]. Most of these strains have already been identified in environments polluted by hydrocarbons [10,[27][28][29]. Liang et al (2014) also identified a strain of Pseudomonas sp.…”
Section: Characterization Of Gram-bacteriamentioning
confidence: 99%
“…However, these physicochemical methods are acquainted with problems such as incomplete decomposition or breakdown of contaminants, and moreover, the technologies are comparatively expensive when compared to biodegradation (Das andChandra, 2011Benchiuk andChibani, 2017). Although, freely suspended cells used in biodegradation have limited capacity, recently the new trend which has gained more attention is cell immobilization on solid support or adsorbent (Sreenivasulu, 2012), and many of these technologies have been used successfully for crude oil bioremediation.…”
mentioning
confidence: 99%